ENTREPRENEURS’ CHALLENGE IN DEVELOPING FAST FOOD RESTAURANT: A CASE OF FK CHICKENIN JAKARTA - Farida Komalasari; Vallent Vallent (President University, 2021)
Increasing number of fast food restaurant encourages entrepreneurs to compose a suitable strategy in developing their business. Entrepreneurs should know well about the customers satisfaction factors of fast food restaurant and its impact on customers’ purchase intention. Knowing the influence of dineserve’s variables (food.quality, atmosphere, servicesquality,.convenicence.and.price) on customers’.satisfaction and purchase intention in fast food restaurant is needed. Therefore, this research’s objectives are to indentify the influence of dineserve on.customer satisfaction and to identify the influence of customers’.satisfaction on purchase intention of FK Chicken products. A quantitative analysis is carried out through circulating an online questionnaire, which consists of 37 statements.There are 250respondents which are choosen using purposive sampling and snowball sampling from its population. The population are people who have ever purchase of FK Chicken products in Indonesia. After checking the validity & reliability, SEM is used for model fit testing, hypothesis testing and R-Square analysis. The result shows thatthe product quality data is not valid, so it is excluded from the inferential analysis. The all four dineserve’s variables positively influence customer satisfaction and also customer satisfaction influences purchase intention. Therefore, an entrepreneur should focus on the way how to improve customers’s saticfaction by providing an interesting atmosphere, giving better servicesquality, improving the convenicence,.and offering an affordable.price. Keywords: Dineserve, Customer Satisfaction, Purchase Intention, Fast Food Restaurant, Indonesia